All-dry chemical engineering for high-performance packaging materials based on biodegradable polymer composites - Lee, Sangwoon; Kim, Jaeyun; Hong, Sung Woo; Bang, Joona; Park, Jong Hyuk (Elsevier BV, 2024)
As plastic waste from packaging continues to pose a serious threat to the environment, demand for naturally degradable packaging materials, such as biodegradable polymers, is increasing. However, packaging materials derived from biodegradable polymers often lack the mechanical and barrier properties required to replace conventional plastics. To address this issue, we propose an all-dry chemical engineering process to prepare high-performance biodegradable polymer composites incorporating cellulose nanofiber (CNF). Mechanochemistry (MC) is emerging as an effective method to induce chemical reactions between components using mechanical force under dry conditions. Through the MC process, we silanize CNFs and facilitate their chemical interaction with polybutylene succinate (PBS) matrix. This approach resolves the long-standing problem of CNF aggregation without using compatibilizers or solvents. The resulting PBS composite containing 3 wt% CNF exhibits improved mechanical and barrier properties comparable to polyethylene terephthalate, attributed to the formation of a uniform CNF network. Furthermore, its transparency and biodegradability demonstrate promising potential for replacing conventional packaging materials. Consequently, our study can offer a pathway to high-performance packaging materials based on biodegradable polymers, achieved through an environmentally and economically sustainable all-dry process. This contribution aligns with global efforts aimed at minimizing environmental damage from packaging waste.